Clinical implications of lumbar developmental spinal stenosis on back pain, radicular leg pain, and disability. (1st January 2021) - Lai, Marcus Kin Long; Cheung, Prudence Wing Hang; Samartzis, Dino; Karppinen, Jaro; Cheung, Kenneth Man Chee; Cheung, Jason Pui Yin
Abstract : Aims: To study the associations of lumbar developmental spinal stenosis (DSS) with low back pain (LBP), radicular leg pain, and disability. Methods: This was a cross-sectional study of 2, 206 subjects along with L1-S1 axial and sagittal MRI. Clinical and radiological information regarding their demographics, workload, smoking habits, anteroposterior (AP) vertebral canal diameter, spondylolisthesis, and MRI changes were evaluated. Mann-Whitney U tests and chi-squared tests were conducted to search for differences between subjects with and without DSS. Associations of LBP and radicular pain reported within one month (30 days) and one year (365 days) of the MRI, with clinical and radiological information, were also investigated by utilizing univariate and multivariate logistic regressions. Results: Subjects with DSS had higher prevalence of radicular leg pain, more pain-related disability, and lower quality of life (all p < 0.05). Subjects with DSS had 1.5 (95% confidence interval (CI) 1.0 to 2.1; p = 0.027) and 1.8 (95% CI 1.3 to 2.6; p = 0.001) times higher odds of having radicular leg pain in the past month and the past year, respectively. However, DSS was not associated with LBP. Although, subjects with a spondylolisthesis had 1.7 (95% CI 1.1 to 2.5; p = 0.011) and 2.0 (95% CI 1.2 to 3.2; p = 0.008) times greater odds to experience LBP in the past month and the past year, respectively. Conclusion: This large-scale study identified DSS as a risk factor of acute and chronic radicular leg pain. DSS was seen in 6.9% of the study cohort and these patients had narrower spinal canals. Subjects with DSS had earlier onset of symptoms, more severe radicular leg pain, which lasted for longer and were more likely to have worse disability and poorer quality of life. In these patients there is an increased likelihood of nerve root compression due to a pre-existing narrowed canal, which is important when planning surgery as patients are likely to require multi-level decompression surgery. Cite this article: Bone Joint J 2021;103-B(1):131–140.